Cluster of Differentiation 4, Serum Malondialdehyde and Immunoglobulin M concentrations in ageing of apparently healthy humans in Keffi, Nigeria (FULafia Journal of Science and Technology, 2018)
This study evaluated blood samples of 150 adults of age range 30-79 years with 96 males and 54 females on immunology indices; malondialdehyde (MDA), immunoglobin M (IgM) and cluster of differentiation 4 (CD+ 4). Serum MDA concentration significantly (p